Hubungan Kecemasan Ibu Tentang Kipi dengan Kelengkapan IDL di Desa Bulujaran Kidul Tegalsiwalan Probolinggo - Nofita Sari; Tutik Ekasari; Iit Ermawati (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Anxiety is a reaction to fear of or in a situation, anxiety shows a tendency to perceive a situation as threatening or stressful (stressful situation), Immunization is a health service that aims to protect individuals from diseases that can be prevented by immunization is an important component of primary health services and plays a major role in reduce the mortality rate of toddlers. The purpose is to find out the corellation between maternal anxiety about AEFI and IDL completeness. A type of correlational analytical research with a cross sectional research design.The research was conducted in Bulujaran Kidul Village on June 10, 2024 by collecting repondents for the posyandu event. The population was 173 respondents. The study used technique. So that the sample was obtained by 49 respondents using the slovin formula that meets the inclusion requirements. The instrument uses an emergency questionnaire and an IDL completeness questionnaire using a KIA book. Data analysis using Chi-Square. The results of the study used showed that of anxiety data in mothers were mostly in the severe category of 23 respondents (47%). and the behavior of IDL completeness was mostly incomplete in the category of 38 respondents (78%). The results of the Chi-Square test were obtained that the p-value = 0.002 so that the p-velue value ≤ α = 0.05. This shows the corellation between maternal anxiety about AEFI and IDL completeness. It is hoped that mothers will gain knowledge about the importance of IDL for children's gaps in the future and it is hoped that mothers will support their families to always make good decisions.